Black Soldier Fly Larvae Cultivation: A Sustainable Solution for Organic Waste in in Tanjung Karang and Taman Dato’ Harun Communities in Malaysia - Suhartini, Sri (Journal of Innovation and Applied Technology, 2025)
Malaysia faces significant challenges in food waste management, with approximately 8,000 tons of food waste generated daily, only 5% of which is treated. To address this issue, the "Doktor Mengabdi Pengembangan Kemitraan" and "KKN Tematik" programs introduced Black Soldier Fly (BSF)-based organic waste management in Tanjung Karang and Taman Dato’ Harun, Selangor. The program included socialization, BSF cage fabrication, and hands-on training on maggot cultivation. BSF larvae degrade organic waste and produce residue (kasgot) for use as organic fertilizer, while larvae can be processed into animal feed, such as dried maggots. Pre- and post-tests revealed significant knowledge gains: 60.84% in Tanjung Karang and 45.23% in Taman Dato’ Harun. Monitoring showed successful community adoption of BSF cultivation. This initiative not only addresses food waste management but also provides economic opportunities and supports the UN Sustainable Development Goals (SDG 12: Responsible Consumption and Production, and SDG 13: Climate Action).